2011
DOI: 10.1590/s2236-89062011000400008
|View full text |Cite
|
Sign up to set email alerts
|

Flora Polínica da Reserva do Parque Estadual das Fontes do Ipiranga (São Paulo, Brasil): Família: 136-Solanaceae

Abstract: -(Pollen flora of "Reserva do Parque Estadual das Fontes do Ipiranga" (São Paulo, Brazil). Family: 136-Solanaceae). Pollen grains of 12 genera and 41 species of Solanaceae occurring in the "Reserva do Parque Estadual das Fontes do Ipiranga" were examined: Acnistus arborescens (L.) Schlecht., Athenaea picta (Mart.) Sendtn., Brunfelsia latifolia Benth., Brunfelsia pauciflora IntroduçãoEste trabalho faz parte do projeto elaborado por Melhem et al. (1984), que visa realizar a caracterização morfológica dos grãos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
0
6
0
5
Order By: Relevance
“…O presente trabalho faz parte do projeto elaborado por Melhem et al (1984), que visa caracterizar morfologicamente os grãos de pólen das famílias ocorrentes na Reserva do Parque Estadual das Fontes do Ipiranga (PEFI), com o objetivo de complementar os levantamentos taxonômicos realizados na mesma área segundo planejamento apresentado por Melhem et al (1981) e finalizado em Nakajima et al (2001). O formato atual segue Cruz- Barros & Souza (2005). Devido à sinonimização do gênero Chamaesyce em Euphorbia, as espécies tratadas em Chamaesyce na monografia da família Euphorbiaceae para o Parque Estadual das Fontes do Ipiranga (Cordeiro 1989), aparecem no presente trabalho em Euphorbia.…”
Section: Introductionunclassified
“…O presente trabalho faz parte do projeto elaborado por Melhem et al (1984), que visa caracterizar morfologicamente os grãos de pólen das famílias ocorrentes na Reserva do Parque Estadual das Fontes do Ipiranga (PEFI), com o objetivo de complementar os levantamentos taxonômicos realizados na mesma área segundo planejamento apresentado por Melhem et al (1981) e finalizado em Nakajima et al (2001). O formato atual segue Cruz- Barros & Souza (2005). Devido à sinonimização do gênero Chamaesyce em Euphorbia, as espécies tratadas em Chamaesyce na monografia da família Euphorbiaceae para o Parque Estadual das Fontes do Ipiranga (Cordeiro 1989), aparecem no presente trabalho em Euphorbia.…”
Section: Introductionunclassified
“…Hunz. (Bernardello & Lujan 1997;Cabrera & Cuadrado 2001;Silva et al 2003;Batista-Franklin & Gonçalves-Esteves 2008;Cruz-Barros et al 2011). More insightful discussion should take place about the use of the term geniculum in Solanaceae palynology.…”
Section: Discussionmentioning
confidence: 99%
“…The pollen morphology of various genera and species of Solanaceae has been described by different types of studies: Pollen morphology of the family in general (Guang-Fang et al 1985;Bernadello & Luján 1997;Khatamsaz & Zangirian 1998;Batista-Franklim & Gonçalves-Esteves 2002;Rojas & Laportte 2004;Rodrigues et al 2016;Dhanya & Devipriya 2016); Pollen morphology of Cestrum or Solanum (Murry & Eshbaugh 1971;Silva et al 2003;Al-Quran 2004;Perveen & Qaiser 2007;Batista-Franklim & Gonçalves-Esteves 2008;Lashin 2011;Kumar et al 2015;Vignoli-Silva et al 2015;Song et al 2018) and Pollen flora of some species (Erdtman 1952;Chung & Huang 1972;Salgado-Labouriau 1973;Rao & Ling 1974;Punt & Monna-Brands 1977;Roubik & Moreno 1991;Velásquez & Rangel 1995;Melhem et al 2003;Barth & Duarte 2008;Cruz-Barros et al 2011;Mercado-Gómez et al 2013;Silva et al 2014Silva et al , 2016Lorente et al 2017). These authors have observed the differences regarding pollen grain aperture and ornamentation of the exine, concluding that the family is eurypalynous.…”
Section: Introductionmentioning
confidence: 99%